Grounds for the application of judicial discretion in criminal proceedings - Вапнярчук, В. В. (Problems of legality, 2014)
This paper analyzes the essence of two of the three grounds specified by the author for the use of judicial discretion (discretion) in court proceedings. In particular, investigate the nature of discretionary (ad hoc or discretionary) with respect to the law and determined whether alternative sanctions mandatory rules of law (law of nature, especially the consolidation of the law, the types and cost). Expressed and reasoned opinion on the unreasonableness of reference to the reasons for judicial discretion legal gaps and conflicts in legislation, regulations and scientific advisory and methodical.